Nasal, oral and ear swabs for canine visceral leishmaniasis diagnosis: new practical approaches for detection of Leishmania infantum DNA. - Sidney de Almeida Ferreira; Gregório Guilherme Almeida; Soraia de Oliveira Silva; Gabriela Peixoto Vogas; Ricardo Toshio Fujiwara; Antero Silva Ribeiro de Andrade; Maria Norma Melo (Public Library of Science (PLoS), 2013)
Background The aim of this study was to evaluate the potential use of nasal, oral, and ear swabs for molecular diagnosis of canine visceral leishmaniasis (CVL) in an endemic urban area in Brazil. Methodology/principal findings Sixty-two naturally infected and ten healthy dogs were enrolled in this study. Bone marrow aspirates, peripheral blood, skin biopsy, and conjunctival, nasal, oral, and ear swabs were collected. All samples, except blood, were submitted to conventional PCR (cPCR) and quantitative real time PCR (qPCR) to detect and quantify Leishmania infantum DNA, respectively. All dogs were submitted to thorough clinical analysis and were included based on a combination of serological (ELISA immunoassay and immunofluorescent antibody test) and parasitological methods. The cPCR positivity obtained from nasal swab samples was 87% (54/62), equivalent to those from other samples (P>0.05). Positive results were obtained for 79% (22/28) in oral swabs and 43% (12/28) in ear swab samples. A significant difference was observed between these data (P=0.013), and the frequency of positive results from oral swab was equivalent to those from other samples (P>0.05). The use of ear swab samples for cPCR assays is promising because its result was equivalent to skin biopsy data (P>0.05). The qPCR data revealed that parasite loads in mucosal tissues were similar (P>0.05), but significantly lower than the parasite burden observed in bone marrow and skin samples (P<0.05). Conclusions Nasal and oral swab samples showed a high potential for the qualitative molecular diagnosis of CVL because their results were equivalent to those observed in samples collected invasively. Considering that mucosae swab collections are painless, noninvasive, fast and practical, the combination of these samples would be useful in massive screening of dogs. This work highlights the potential of practical approaches for molecular diagnosis of CVL and human leishmaniasis infections.